Business and peace in the Niger Delta: what we know and what we need to know. Issue 1 (2nd January 2017) - Idemudia, Uwafiokun
ABSTRACT: The global restructuring of state–society relationships driven by neoliberal logic has not only allowed for the taming of the 'state', which has paradoxically accentuated its inadequacies, but has also facilitated, for better or for worse, the emergence of business – especially transnational corporations – as a major political force in global governance. Consequently, while the issues of peace and conflict have traditionally been the concern of governments, businesses are now increasingly being expected to make peace and conflict their concern. However, despite claims and counterclaims that businesses can be moneymakers and peacemakers, analyses of the relationship between business and peace remain largely embryonic. This paper seeks to contribute to this emerging business and peace debate by drawing on insights from the Niger Delta conflict to ascertain what we know and what we need to know if businesses are to become peacemakers in conflict zones in Africa.